PENGARUH PENAMBAHAN NATRIUM METABISULFIT TERHADAP DERAJAT PUTIH TAPIOKA - Husniati Husniati (Jurnal Dinamika Penelitian Industri, 2010)
This research aims to study effect of adding sodium metabisulfite ( natrium metabisulfit ) in improving whiteness degree of tapoca as required by SNI 01-3452-1993. Tapioca starch in this research is produced without treatment (treatment ) and some additional treatment of deifferent concentrations of natrium metabisulfit.result show s whiteness degree determination obtained without the addition of natrium metabisulfit was 90,30% whereas with natrium metabislulfit  0,1%;0,2%;0,5%; and 1,0% respectively are 91,8%;94,9%;95,7%; and 96,2%. Form perception of amylograph indicate that additional 0,2% natrium metabisulfit didn’t significantly influence to the funsional properties compared to treathment sample without treatment. Physicochemical proretis obtained of addition of 0,2% natrium metabisulfit can deciline stratch content 2 until 4%. It conclouded that 0,2% netrium metabisulfit are inhibitor to prevent brownig reaction on tapioca.the adding of natrium metabisulfit until 0,2% didn’t give effect for functional properties as native starch.